2021
DOI: 10.1007/s10654-021-00758-0
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine hesitancy due to vaccine country of origin, vaccine technology, and certification

Abstract: Vaccine hesitancy is a global health threat which may hinder the widespread acceptance of several COVID-19 vaccines. Following the collection of 2470 responses from an anonymous questionnaire distributed between October and November 2020 across Israel, we analyzed the responses of physicians, life science graduates (biology, virology, chemistry, etc.), and the general public to whether they would obtain a COVID-19 vaccine with particular vaccine characteristics such as vaccine country of origin, technology, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 3 publications
1
17
0
Order By: Relevance
“…Country of origin of vaccine was also previously reported to be an important factor. Respondents from Israel preferred vaccines manufactured in USA/UK rather than China [61], while respondents from China expressed preference for China-made over foreign-made COVID-19 vaccines [62]. With the world preparing to ease travel restrictions when the pandemic subsides, different countries have imposed different travel restrictions that only allow those vaccinated with specific vaccines developed in specific countries through their borders [63].…”
Section: Discussionmentioning
confidence: 99%
“…Country of origin of vaccine was also previously reported to be an important factor. Respondents from Israel preferred vaccines manufactured in USA/UK rather than China [61], while respondents from China expressed preference for China-made over foreign-made COVID-19 vaccines [62]. With the world preparing to ease travel restrictions when the pandemic subsides, different countries have imposed different travel restrictions that only allow those vaccinated with specific vaccines developed in specific countries through their borders [63].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the slightly greater preference for Vaccine A among the unvaccinated may reflect the lesser burden of a one-shot regimen. However, the differences are substantively small and largely mirror past research finding that the number of required shots and vaccine type have a relatively modest effect on vaccine choice [ 9 , 21 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 73%
“…Several studies have examined the influence of vaccine type on public preferences. An analysis of public opinion in Israel showed greater hesitancy to an mRNA vaccine [ 27 ], though an analysis of students in Italy suggested greater hesitancy toward a viral vector reverse [ 28 ]. On the other hand, a study in the United States showed little evidence that vaccine type significantly influenced vaccine choice [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attention, scrutiny, and stakes are clearly much higher during this public health crisis than ever before in recent decades and therefore, there are several factors of vaccine hesitancy that have become more prominent in general. For example, new fronts of vaccine hesitancy were introduced into the mainstream as a survey conducted in Israel found that determinants of trust levels towards Covid-19 vaccines have increasing degrees of importance within geographical and technological dimensions, whereby whether the vaccine is coming from China, the US, or Russia and whether it employs mRNA, Vector, or traditional technologies also plays a role (Dror et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%